PERANCANGAN APLIKASI AKADEMIS BERBASIS ANDROID PADA SMP KARTIKA XI DI JAKARTA TIMUR - Taufiq Septryana; Yuli Haryanto; Andi Prastomo (Universitas Palangka Raya, 2023)
SMP Kartika XI is one of the educational entities that is obliged to carry out academic activities. With an android-based academic application, it can help in carrying out these academic activities to be more efficient and cost-effective. Therefore, this study seeks to provide a solution to the problem of routines that are still not effective at Kartika XI Middle School. Researchers use the grounded research method to find out the existing problems, equipped with observations and interviews to find data and validation so that existing problems can be solved accurately. The system design is built using the Typescript programming language, the Ionic framework, and Golang for the server side. As for the database using MYSQL. The results of this study are android-based academic applications intended for teachers and students to be able to perform activities such as input attendance, view attendance history, subject schedule information, grades, and the latest news about the school.